The Syrian Model’s Evolution Into A Global Scene: Power Play Vs. Dominance (Revue El-Wahat pour les Recherches et les Etudes, 2023)
Abstract:The Present Article Gives A Detailed Account Of The Syrian Uprising From Its Early Days To Its Evolution Into A Global Scene Of Flagrant Foreign Intervention. The Article Displays The Crisis As It Went Through Different Tumultuous Phases To Understand The Syrian People's Scattering As Finally, The Article Tries To Name The Disparate Involved Fronts. The Article Also Discusses The Starting Point Considering All The Interference And Conflicting Sides Which Is The Value Of Syria. In The Middle Of The Prone Warring Context Not Only Within The Country Itself Counting The Rise Of The Islamic State But Also In The Whole Area Of The Levant As The Article Analyses How The Country Was Used For The Russian Political Pride And The U.S Invisible Hegemony.Keywords: Intervention, Syria, Russia, The U.S, People’s Scattering.